2016
DOI: 10.1530/eje-15-1226
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological predictive factors in the early remission of corticotroph pituitary macroadenomas in a tertiary referral centre

Abstract: ObjectiveCorticotroph macroadenomas are a rare cause of Cushing's disease (CD), but their properties are not well-recognised. The aim of this study was to evaluate the clinical and pathological aspects of corticotroph macroadenomas with particular emphasis on proliferation markers and their associations with the efficacy of surgical treatment.DesignA prospective cohort study was conducted in a tertiary referral centre in Poland.MethodsIn total, 59 patients with CD (20 macroadenomas and 39 microadenomas) were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
35
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 39 publications
3
35
0
1
Order By: Relevance
“…We assessed the Ki-67 labeling index in corticotroph tumors with sufficient samples only. Despite slightly higher averages of Ki-67 in SGCTs, the difference was not statistically significant; and similar results were shown in the study reported by Witek et al (12). However, the eye-balling method we used to evaluate Ki-67 is no longer accepted in the field of neuroendocrine neoplasms including those of pituitary origin and also a minimum of 500 tumor cells should be counted for this examination.…”
supporting
confidence: 80%
See 2 more Smart Citations
“…We assessed the Ki-67 labeling index in corticotroph tumors with sufficient samples only. Despite slightly higher averages of Ki-67 in SGCTs, the difference was not statistically significant; and similar results were shown in the study reported by Witek et al (12). However, the eye-balling method we used to evaluate Ki-67 is no longer accepted in the field of neuroendocrine neoplasms including those of pituitary origin and also a minimum of 500 tumor cells should be counted for this examination.…”
supporting
confidence: 80%
“…It is reported in the literature that the majority of corticotroph tumors were densely granulated (3,(6)(7)(8)10,12). However, in a recent study, Mete et al (13) reported the frequency of SGCTs and DGCTs in their cohort as 29% and 47%, respectively and interpreted this result as an…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…8,9,14,18 Utilization of the pseudocapsule among macroadenomas, howev-er, has been discussed only in limited series and with little to no emphasis on surgical technique and with contrasting conclusions regarding the efficacy of pseudocapsular resection. 12,19,23 Instead, traditional resection of macroadenomas, via either an endoscopic or microscopic approach, has typically used a piecemeal resection technique. 1,6 The piecemeal technique, however, results in reduced visibility of the tumor margins as the tumor is centrally decompressed and the remaining tumor descends and the normal gland expands.…”
Section: Discussionmentioning
confidence: 99%
“…[3,812] While macroadenomas have relatively lower remission rates of 12.5% to 71.1%, with more operative complications and higher recurrence rates. [8,9,1319] Cavernous sinus invasion is another unfavorable prognostic factor for transsphenoidal surgery. [3] Specifically, the reported remission rates among ACTH-secreting pituitary adenomas with cavernous sinus invasion range from 0% to 60%.…”
Section: Introductionmentioning
confidence: 99%